Casos de Rabia Urbana en el Estado Zulia - Venezuela. Período 2007 - Julio 2013 - Fuentes M Belkis; Panunzio R Amelia; Villarroel R Francis; Ávila L Ayarí; Pírela S Elsa; Parra de C Irene; Molero, Milagros; Prieto, Yelitza (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2014)
Abstract: Rabies is a lethal zoonosis, and due to its wide distribution around the world, it constitutes a relevant problem for the public health system. It is an acute viral encephalomyelitis, transmitted by the bite of an infected animal. Rabies is endemic in the State of Zulia and has been a health problem of high social impact. The objective of this study was to determine the cases of urban rabies in the State of Zulia from 2007 to July 2013 and to identify its distribution according to municipalities and species. The research is descriptive; a documentary review of records from the Regional Zoonosis Coordination of the State of Zulia was carried out for the period under study. From the 2130 diagnosed samples, a total occurrence of 117 (5.49%) cases of urban rabies was found among the different municipalities; 116 of these cases were diagnosed in animals and one in a human being, a three-year-old girl from the Maracaibo Municipality. The highest occurrence was in the municipalities of Maracaibo (42.73%) and Lagunillas (23.08%). The study recommends coordinating extension activities in communities, based on responsible pet possession and handling as well as the need to optimize vaccination procedures as a measure to eliminate the risk of infection. Resumen: La rabia es una zoonosis mortal y debido a su amplia distribución en el mundo, constituye un problema de relevancia en la salud pública; es una encefalomielitis viral aguda, transmitida por mordedura de un animal infectado. El Estado Zulia tiene carácter endémico y ha sido un problema de salud de alto impacto social. El objetivo de este estudio fue determinar los casos de rabia urbana en el Estado Zulia en el período 2007 - Julio 2013 e identificar su distribución según municipios y especies. La investigación fue de tipo descriptivo, se realizó revisión documental de los registros de la Coordinación Regional de Zoonosis del Estado Zulia del período estudiado. De las 2130 muestras diagnosticadas se observó una ocurrencia total de 117 (5,49%) casos de rabia urbana en los diferentes Municipios, de los cuales 116 se diagnosticaron en animales y 1 en humano, niña de 3 años perteneciente al municipio Maracaibo; la mayor ocurrencia fue en los municipios Maracaibo (42,73%) y Lagunillas (23,08%). Se recomienda coordinar actividades de extensión en comunidades basadas en la tenencia y manejo responsable de las mascotas, así como la necesidad de optimizar la vacunación como medida para eliminar el riesgo de infección.